2001
DOI: 10.1176/appi.ajp.158.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists Disciplined by a State Medical Board

Abstract: Organized psychiatry has an obligation to address sexual contact with patients and other causes for medical board discipline. This obligation may be addressable through enhanced residency training, recertification exams, and other means of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
5
34
0
Order By: Relevance
“…Gartrell et al (1986) found 7% of male and 3% of female psychiatrists reported sexual contact with patients. More recent data from the USA suggest that those engaged in intense psychotherapy are at higher risk of this behaviour (Morrison et al, 2001). The General Medical Council (GMC) strikes off a small number of psychiatrists each year for inappropriate relations with patients, and many of these are psychotherapists.…”
Section: Are Psychotherapies Safe?mentioning
confidence: 99%
“…Gartrell et al (1986) found 7% of male and 3% of female psychiatrists reported sexual contact with patients. More recent data from the USA suggest that those engaged in intense psychotherapy are at higher risk of this behaviour (Morrison et al, 2001). The General Medical Council (GMC) strikes off a small number of psychiatrists each year for inappropriate relations with patients, and many of these are psychotherapists.…”
Section: Are Psychotherapies Safe?mentioning
confidence: 99%
“…3 It has been postulated that these specialties face a greater risk of discipline because they practice mainly in isolation, have frequent patient interactions, and can develop intense physician-patient relationships. 7 Such intimate relationships can potentially blur physical and sexual boundaries, which may account for the fact that psychiatrists and family physicians are more likely to receive discipline for sexual improprieties and boundary issues. 4,8 Apart from the subspecialty of chronic pain medicine, the nature of the relationship between an anesthesiologist and patient is much different and may account for the observed disciplinary rates.…”
Section: Discussionmentioning
confidence: 99%
“…The total physician percentage is based on a calculated field of data compiled from the Canadian Institute for Health Information (CIHI) and the Canadian Post-M.D. Education Registry (CAPER), i.e., the average number of physicians, including both independent practitioners and resident physicians, during 2000-2011 7,8 *The total number of physicians disciplined in each category is based on investigation-based tallies. The total physician percentage is based on a calculated field of data compiled from the Canadian Institute for Health Information (CIHI) and the Canadian Post-M.D.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an area which has frequently been explored in psychiatry is sexual misconduct. In 2001, Morrison and Morrison [38] studied physicians disciplined by the California Board of Medicine during a 30-month period. Female physicians were underrepresented among disciplined physicians.…”
Section: Who Are the Difficult Colleagues?mentioning
confidence: 99%